The Role of the School Principal In Improving Teacher Discipline at the Madrasah Aliyah in Indonesia - Ivan Riyadi; Diah Novita Sari (Presscience, 2023)
Supervision carried out by the principal means carrying out the leadership of the management function, where the supervision of the principal is one of the determining factors in achieving educational goals. In this study, the researcher wanted to see the process of supervision carried out by the principal in improving teacher discipline. This study used qualitative research methods. Sources of data from this study were the principal and 2 teachers. The data collection techniques in this study used observation, interviews and documentation. The data analysis technique was done by means of data reduction, data display, data leveraging and drawing conclusions. The results of this study indicate that it is quite good with several aspects, namely the procedure stage, standard stage, improvement and accuracy. It can be said that the supervision of the principal at Madrasah Aliyah Paradigma through several aspects, namely First, the Procedure Stage carried out is quite good. Second, the Standard stage was carried out well, the principal supervised the teacher by looking at the attendance of each existing class, checking the learning tools before the new teaching began. Third, improvements, if the teacher makes mistakes in doing a job or is not disciplined at work, there will be improvements. Fourth, the research was carried out with the principal in uniting teachers at Madrasah Aliyah Paradigma. In accordance with the Decree of the division of work tasks that have been given. Where there are two factors, namely supporting and inhibiting factors. The supporting factor for the supervision of discipline teachers at Madrasah Aliyah Paradigma is the absence of teacher attendance and return. The inhibiting factor for supervising teacher discipline at Madrasah Aliyah Paradigma is the head of the madrasa who has a work agenda outside of teaching and learning hours at the madrasah.